Financial Literacy, Financial Attitude, Education Level and Lifestyle on Personal Financial Management of Students in Sidoarjo - Ardiandana, Mohammad Rengga; Sriyono, Sriyono; Setiyono, Wisnu Panggah (Jurnal Ilmu Manajemen Advantage, 2024)
Today, students are expected to have a better understanding, skills, and confidence, especially in managing their personal finances well. However, some students consider that financial planning does not need to be studied because it is considered a daily activity. This study aims to determine whether financial literacy, financial attitude, education level and lifestyle affect the personal financial management of students in Sidoarjo. This study used quantitative methods. The population in this study was 23,039 and the sample amounted to 100 respondents. The sampling technique uses random sampling. The type of data used is primary and secondary by spreading questionnaires through google forms. The results of this study are financial literacy, financial attitude, education level and lifestyle have a positive and significant effect on the personal financial management of students in Sidoarjo.